RETURN SAHAM : PRICE TO BOOK VALUE (PBV), RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE) DAN UKURAN PERUSAHAN PADA PERUSAHAAN FOOD AND BEVERAGE - Azizah, Siti Nur; Hariani, Lilik Sri; Dianawati, Eris (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2019)
The purpose of this study was to determine the effect of financial ratios, among others: Price to Book Value (PBV), Return On Assets (ROA), Return On Equity (ROE) and company size on stock returns, both simultaneous and partial balance. This research was conducted using a sample of 12 food and beverage companies on the Indonesia Stock Exchange by determining the sample taken (purposive sampling) because there were certain considerations over a 4-year period (2014-2017). This study uses multiple linear regression methods with the SPSS 22 program. The results of this study indicate that there is simultaneously an influence between Price to Book Value (PBV), Return On Assets (ROA), Return On Equity (ROE) and company size on stock returns. And partially Price to Book Value (PBV) and Return On Assets (ROA) have no effect on stock returns, while Return On Equity (ROE) and company size on stock returns have a significant effect on stock returns.